2010
DOI: 10.1021/om900938m
|View full text |Cite
|
Sign up to set email alerts
|

Dinuclear Dicyclopentadienyl Titanium Complexes with Bridging Cyclopentadienylsiloxo Ligands

Abstract: Addition of 1 equiv of TlCp to compound [(TiCl 2 ) 2 (μ-{(η 5 -C 5 Me 4 SiMeO) 2 (μ-O)})] (A) at 80 °C gave a mixture with different molar ratios of the two possible isomers of [(TiClCp)(TiCl 2 )(μ-{(η 5 -C 5 Me 4 SiMeO) 2 (μ-O)})] (1). Reaction of compound A with 2 equiv of TlCp at 80 °C afforded [(TiClCp) 2 (μ-{(η 5 -C 5 Me 4 SiMeO) 2 (μ-O)})] (2as) as the unique reaction product. Each Cp ligand of 2as is located in different positions anti and syn with respect to the Si-O-Si bridge. However, a mixture of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 73 publications
(103 reference statements)
0
2
0
Order By: Relevance
“…As it appeared that obtaining methyl-aryloxy complexes 3 ′ was going to be a challenging task, we wondered whether cationic aryloxy Ti complexes 4 could be obtained directly from 3 . Indeed B­(C 6 F 5 ) 3 and [Et 3 Si]­[B­(C 6 F 5 ] 4 have been used to abstract Cl from Ti complexes derived from titanocene, , and Wass recently showed that sequential reduction and oxidation of [Cp 2 TiClOAr] complexes afforded [Cp 2 TiOAr]­[B­(C 6 F 5 ) 4 ] species . When complexes 3a and 3c were mixed with B­(C 6 F 5 ) 3 in C 6 D 6 , the solutions immediately turned from red-orange to red-brown ( 3a , 3c ) or deep purple ( 3b ).…”
Section: Resultsmentioning
confidence: 99%
“…As it appeared that obtaining methyl-aryloxy complexes 3 ′ was going to be a challenging task, we wondered whether cationic aryloxy Ti complexes 4 could be obtained directly from 3 . Indeed B­(C 6 F 5 ) 3 and [Et 3 Si]­[B­(C 6 F 5 ] 4 have been used to abstract Cl from Ti complexes derived from titanocene, , and Wass recently showed that sequential reduction and oxidation of [Cp 2 TiClOAr] complexes afforded [Cp 2 TiOAr]­[B­(C 6 F 5 ) 4 ] species . When complexes 3a and 3c were mixed with B­(C 6 F 5 ) 3 in C 6 D 6 , the solutions immediately turned from red-orange to red-brown ( 3a , 3c ) or deep purple ( 3b ).…”
Section: Resultsmentioning
confidence: 99%
“…Since 2004, notable examples of this approach have been reported using the following Lewis acids B(C 6 F 5 ) 3 , [198,210] Al(C 6 F 5 ) 3 , [199,210] Al(OC(CF 3 ) 3 ) 3 , [144,145] Al(OC-(C 5 F 10 )C 6 F 5 ) 3 , [144] Ga(C 6 F 5 ) 3 , [155] and TMS-F-Al(OR F ) 3 (TMS = trimethylsilyl) [211] as well as the triarylboranes FcB-(o-tol) 2 ,F cB(o-Xyl) 2 ,F cBMes 2 , [212,213] PhBMes 2 , [214] or B(o-C 6 F 5 C 6 F 4 ) 3 [155] (where Fc = ferrocene; o-tol = 2-(CH 3 )C 6 H 5 ; oxyl = 2,6-(CH 3 ) 2 C 6 H 4 ;M es = 1,3,5-(CH 3 )C 6 H 4 ).…”
Section: Strong Lewis Acidsmentioning
confidence: 99%